Aspherical Weight Test for Mixed Monoid Presentation - Tay, Choo Chuan; Ahmad, Abd Ghafur (Journal of Institute of Mathematics & Computer Science, Kolkata, India, 2008)
This paper constructs generalized left and right graph for mixed monoid presentation. Then the asphericity is given.